Accounting of In-kind Contributions in European Research Infrastructure Consortia (ERICs) - The Case of the European Spallation Source ERIC - Ohad Graber-Soudry; Florian Weissbach; Maja Jensen (Research Ideas and Outcomes)
The European Spallation Source ERIC relies on in-kind contributions from its Members, including technical components, R&D and services, which are vital to its construction and operation. The complex nature and delivery of in-kind contributions have posed significant accounting challenges. Following a comprehensive review in collaboration with external advisors, the European Spallation Source ERIC has adopted a harmonised approach that aligns the treatment of in-kind contributions with cash contributions, enhancing transparency towards stakeholders, compliance with accounting principles and the robustness of financial reporting. The experience of the European Spallation Source ERIC in addressing these complexities offers valuable insights for other ERICs and organisations with similar scopes, promoting effective and transparent management of in-kind contributions. This commentary aims to contribute to the broader understanding of managing in-kind contributions by sharing the European Spallation Source ERIC's experience and lessons learned.